Study on the influence of volume size of the milling jar in purifying Tronoh silica sand using ball milling process - Hashim, N. (American Institute of Physics Inc., 2015)
Tronoh silica sand is the potential source for the SiO 2 . Purification is an important step in expanding the usage of the Tronoh silica sand. Since the residual impurities are the obstacle in achieving high purity silica, the low speed ball mill will be introduced as a main equipment in purifying Tronoh silica sand. The objective of this study is to understand the influence of volume size of the milling jar in purifying Tronoh silica sand by using ball milling process. The chemical composition of the samples were analyzed by using XRF and SEM. The results showed that the highest purity of the Tronoh silica sand can be achieved by using the 1.0 milling jar. Â© 2015 AIP Publishing LLC.